Organizational Aspects of Development Projects Implementation at the Real Estate Market in Ukraine - Svistun, Lyudmyla; Glushko, Ðlina; Shtepenko, Kateryna (International Journal of Engineering and Technology, 2018)
The article is dedicated to the issues of improving a system of organizational providing of investment constructional activity at the real estate market of Ukraine. The authors suggest modern approaches to organizing different stages of investment and construction process. In particular, legal bases for organizing real estate development project concept design stage are analyzed and the ways of permissible procedures simplifying in construction are defined. Suggestions concerning choice of approaches to evaluating real estate projects development effectiveness of realization are made, where an important place belongs to development land improvement estimation. Real estate development project estimation methodology for various real estate types considering special aspects of conducting marketing research is offered.Â  The article conclusion contains means recommended for implementing by real estate development organizations while designing their strategy of development.Â Â